x = -2 then y = -16
x = -1 then y = -6
x = 0 then y = 4
x = 1 then y = 14
x = 2 then y = 24
0 is the constant of 4, this functions is a pattern of when ever x increases by 1, you add 10 from y starting from 4, example:
x = 5 then y = 5 * 10 + 4 which is y = 54
y = 54 while x = 5 also satisfies the equation.
Same goes for when ever x decreases by 1, example:
x = -5 then y = -5 * 10 + 4 which is y = -46
y = -46 while x = -5 also satisfies the equation.
This question was the pattern illustrated above.
This is derived from when you take -10x+y=4 and solve for y
Simply add 10x to both sides, and you have already isolated the y variable in the equation y = 10x + 4
You can plug the values in for x and solve for y and recognize the same pattern above.